Infusible acrylic thermoplastic resins: Tailoring of chemorheological properties. Issue 40 (23rd May 2019) - Cousins, Dylan S.; Howell, Jackson; Suzuki, Yasuhito; Samaniuk, Joseph R.; Stebner, Aaron P.; Dorgan, John R.
ABSTRACT: Infusible liquid resins that polymerize into a thermoplastic are desirable for many applications. Similar to unsaturated and vinylester thermosetting systems, they consist of polymers dissolved in reactive monomer. This work presents a method to decrease cycle time by tuning the molecular weight and concentration of the predissolved polymer in the resin. Variation of these properties allows precise control of the viscosity which in turn controls the time at which peak exotherm is reached, the maximum temperature for a given part thickness, and cure time. Predictive models for the viscosity dependence on molecular weight, polymer concentration, shear rate, and temperature are developed. Two fiberglass panels are fabricated and tested; one with a lower molecular weight ( M w ~30 kg mol −1 ) poly(methyl methacrylate) dissolved in methyl methacrylate and the second with higher molecular weight ( M w ~500 kg mol −1 ) predissolved polymer in the resin. Mechanical properties are indistinguishable but the lower molecular weight panel cures up to three times faster. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48006. Abstract : Facile viscosity control of reactive infusible thermoplastic resins is demonstrated by alteration of the molecular weight and concentration of the preformed polymer in the resin. Such viscosity control can be exploited to dramatically decrease the production cycle time and reduce cost without compromising the quality or mechanical properties of composite parts which are critical for aviation, wind, and marine applications.